A persistent Hadean–Eoarchean protocrust in the western Yilgarn Craton, Western Australia. (3rd July 2022) - Dröllner, Maximilian; Kirkland, Christopher L.; Barham, Milo; Evans, Noreen J.; McDonald, Bradley J.
Abstract: Deciphering the composition and extent of Earth's earliest continents is hampered by the scarcity of preserved Hadean–Eoarchean material. Here, we report U–Pb and Lu–Hf data of detrital zircon from sediments proximal to the Archean Yilgarn Craton in Western Australia. This detrital cargo, in part derived from the crystalline basement of the southwestern Yilgarn Craton and its conjugate terranes, helps to resolve the ancient substrate of the craton. Zircon Hf isotopes point to a Hadean–Eoarchean crustal vestige that has remained isotopically coherent over 2 Gyr of episodic crustal reworking. Geophysical characteristics suggest a distinct 100, 000 km 2 region of ancient protocrust beneath much of the western Yilgarn Craton, cropping out in the Narryer Terrane. Comparison with global data reveals similar Hf isotope trends in many other cratons documenting the widespread existence of voluminous protocrust and implying extensive reservoir extraction at c. 4, 000–3, 800 Ma.